A socio-technical analysis of software policy in Korea: Towards a central role for building ICT ecosystems. Issue 11 (December 2015) - Kim, Hongbum; Shin, Dong-Hee; Lee, Daeho
Abstract: Software has become a core component of the information and communication technology (ICT) industry. While South Korea makes active software promotion efforts, the performances and outcomes of such attempts have not been remarkable. Applying a socio-technical system framework, in this study we address fundamental problems of the software industry and successive software policies that have been implemented in Korea. Based on in-depth analysis, we suggest implications for more effective and productive software policy. With the aim of spurring a strong shift in the software industry, culture, and society towards a central role for building the ICT ecosystem, we provide suggestions regarding the concept of a social platform, the importance of core technology, and key properties. Other countries can use this study as a reference as they promote their own software industries. Highlights: Problems of software policy in Korea. Effective and productive software policy. Suggestions for software industry, culture, and society.